NBTXR3 improves the efficacy of immunoradiotherapy combining nonfucosylated anti-CTLA4 in an anti-PD1 resistant lung cancer model - Hu, Yun; Paris, Sébastien; Bertolet, Genevieve; Barsoumian, Hampartsoum B.; Wang, Qi; Da Silva, Jordan; Patel, Nalini B.; Nguyen, Nguyen; Doss, Denaha J.; Huang, Ailing; Hsu, Ethan; Leyton, Claudia S. Kettlun; et al. (Frontiers in Immunology, 2022)
The efficacy of immunoradiotherapy consisting of radiation therapy and immune checkpoint blockade relies on effectively promoting the systemic antitumor immune response's activation while simultaneously reducing local factors favoring immune suppression. We previously demonstrated that NBTXR3, a nanoparticle radioenhancer, significantly improved immune responses in a murine anti-PD1-resistant metastatic lung cancer model. We hypothesize that radioactivated-NBTXR3 addition to anti-PD1 and a second-generation anti-CTLA4 could improve treatment effectiveness. To test this hypothesis, we inoculated mice with 344SQR cells in the right and left legs to establish primary and secondary tumors. The primary tumors were intratumorally injected with NBTXR3 nanoparticles on day 7, followed by three fractions of 12 Gy radiation on days 8, 9, and 10. The secondary tumors received two fractions of 1Gy radiation on days 13 and 14. Multiple rounds of anti-PD1, anti-CTLA4 or nonfucosylated anti-CTLA4 were given to the mice. Immune profiling of the tumors revealed that the combination of NBTXR3 with immunoradiotherapy significantly upregulated the activities of a wide range of antitumor immune pathways and reduced the abundance of regulatory suppressor T cells. This combination effectively eradicated the primary and secondary tumors and increased animal survival to 75%. Remarkably, previously treated with NBTXR3-containing treatment, the survivor mice exhibited a long-lasting antitumor memory immune response. This data provides compelling evidence of the efficacy of NBTXR3 to synergize with the immunoradiotherapy approach when combined with an anti-PD1 and multiple checkpoints such as a second generation anti-CTLA4 and show the potential for clinical uses of antitumor immunomodulatory effects of NBTXR3.